2008
DOI: 10.2355/isijinternational.48.1467
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Property of Copper Bearing Eutectoid Steel

Abstract: Fig. 12. Relation between 0.2 % proof stress and lamellar spacing in Base-steel, 1 % Cu-steel and 2 % Cu-steel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Most of the precipitation occurs in the ferrite and at the interface between cementite and ferrite, but a small portion may also occur in the cementite constituent of pearlite. Murakami et al [15) have studied the precipitation of epsilon-Cu during isothermal growth of pearlite in steels (0.8 wt.% carbon, 0.26 wt.% silicon and 0.35 wt.% manganese) alloyed with 0.06, 1.06 and 2.06 wt.% copper. ln the case of the alloy with 2.06 wt.% Cu, they observed that epsilon-Cu precipi tates bath at the ferrite/austenite interface and in ferrite at 923 K (650°C), whereas it precipitates mainly in ferrite at 873 K (600°().…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the precipitation occurs in the ferrite and at the interface between cementite and ferrite, but a small portion may also occur in the cementite constituent of pearlite. Murakami et al [15) have studied the precipitation of epsilon-Cu during isothermal growth of pearlite in steels (0.8 wt.% carbon, 0.26 wt.% silicon and 0.35 wt.% manganese) alloyed with 0.06, 1.06 and 2.06 wt.% copper. ln the case of the alloy with 2.06 wt.% Cu, they observed that epsilon-Cu precipi tates bath at the ferrite/austenite interface and in ferrite at 923 K (650°C), whereas it precipitates mainly in ferrite at 873 K (600°().…”
Section: Resultsmentioning
confidence: 99%
“…Considering the evolution of micro-hardness dur ing heat-treatment demonstrated by Murakami et al [15), an attempt to use differential thermal analysis on the cast irons under study -as previously done for 15-5 PH alloy [13) -was carried out. This was not 1300 .…”
Section: Resultsmentioning
confidence: 99%
“…during pearlite formation (e.g., carbides due to microalloying Ti, V, or Nb, [72][73][74][75] and Cu precipitation [76] ) on austenite-pearlite interface or within pearlite. Preexisting phase changes the composition of austenite from which pearlite forms, hence its thermodynamic driving force.…”
Section: B Influence Of Other Phasesmentioning
confidence: 99%
“…The dispersed and fine Cu-precipitated phase gave the antibacterial ability of copper-bearing steel, through a special antibacterial heat treatment technology in the process. [14,15] The solution treatment provides uniform microstructure and controllable grain size, while the aging treatment leads to the precipitation of a fine phase from the supersaturated solid solution. [1] The regulation of the precipitation behavior of ε-Cu generated during the antibacterial heat treatment has been investigated using different solutions temperatures, aging temperatures, and aging times.…”
Section: Introductionmentioning
confidence: 99%